1993
DOI: 10.1200/jco.1993.11.3.499
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of subcutaneous interleukin-6 in patients with advanced malignancies.

Abstract: A safely tolerated dose of daily subcutaneous IL-6 is 10 micrograms/kg, with hepatotoxicity and cardiac arrhythmia being the dose-limiting toxicities at 30 micrograms/kg. Phase II trials of IL-6 administered subcutaneously daily for at least 7 days for two cycles with an intervening week of rest are recommended for phase II trials. However, patients with extensive replacement of liver by tumor and abnormal liver functions should receive IL-6 therapy with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(72 citation statements)
references
References 18 publications
8
63
0
Order By: Relevance
“…Dosedependent increases in total cholesterol, HDL cholesterol, and triglycerides were observed and were above the normal range in some patients. This finding is concordant with previous reports that administration of recombinant IL-6 decreased serum cholesterol in cancer patients (31,32) and that IL-6-deficient mice showed an increase in triglycerides and very-low-density lipoprotein in the blood in association with suppressed energy expenditure and increased food intake, with no increase in HDL cholesterol (33). However, MRA treatment also increased HDL cholesterol.…”
Section: Anti-il-6r Antibody Therapy In Rasupporting
confidence: 92%
“…Dosedependent increases in total cholesterol, HDL cholesterol, and triglycerides were observed and were above the normal range in some patients. This finding is concordant with previous reports that administration of recombinant IL-6 decreased serum cholesterol in cancer patients (31,32) and that IL-6-deficient mice showed an increase in triglycerides and very-low-density lipoprotein in the blood in association with suppressed energy expenditure and increased food intake, with no increase in HDL cholesterol (33). However, MRA treatment also increased HDL cholesterol.…”
Section: Anti-il-6r Antibody Therapy In Rasupporting
confidence: 92%
“…Thus, in the case of IL-6, the amount of circulating IL-6 is 1/1000 of the total amount of IL-6 produced per day. These estimations are in agreement with the increase of C-reactive protein production after HDM and ASCT (21), C-reactive protein production is controlled by IL-6 in human in vivo (27), and with an efficacy dose of 5 mg/kg/d for recombinant IL-6 in humans (28). Given these data for IL-6, one can anticipate that the increased concentrations of circulating IL-7 and IL-15 at day 8 post-ASCT indicates an increase biological activity of these cytokines in vivo.…”
Section: Discussionsupporting
confidence: 76%
“…45 Furthermore, in clinical studies in which recombinant human IL-6 has been administered to patients, it has been demonstrated that this molecule increases C-reactive protein levels and decreases serum albumin levels. 124 Human pancreatic carcinoma cells secrete IL-6, IL-10, and TGFb in culture. These cytokines work together to inhibit immature monocyte-derived dendritic cell proliferation, and they down-regulate the expression of costimulatory molecules, such as CD40, CD80, and human leukocyte antigen DR.…”
Section: Pancreatic Cancer Preclinical Studiesmentioning
confidence: 99%